Observation of non-thermal electrons outside the SOL in the Wendelstein 7-X stellarator. (October 2022) - Killer, C.; Aleynikov, P.; Biedermann, C.; Dhard, C.P.; Drews, P.; Gao, Y.; Grulke, O.; Jakubowski, M.; Knieps, A.; Kocsis, G.; Naujoks, D.; Puig Sitjes, A.; et al.
Highlights: Non-thermal electrons can be observed far outside the main plasma in W7-X. Occurrence is limited to electron-cyclotron resonance heated plasmas at low density. Electrons cause hot spots on plasma-facing components with considerable heat fluxes. Abstract: Hot spots and bright patterns on plasma-facing components (PFC) in visible light are observed in electron cyclotron resonance heated (ECRH) plasmas at low densities in the stellarator Wendelstein 7-X. The events are often located far outside of any convective plasma loads and led in some cases to damages of diagnostic components, where the interaction zones qualitatively agree with fast particle loss simulations. Reciprocating electric probes indicate that this phenomenon is related to a non-thermal electron population that can have a beam like character, being directed in one parallel direction. Further, the electrons can be trapped on rational flux surfaces and be used to map magnetic islands.